DISIPLIN KERJA PEGAWAI NEGERI SIPIL BAGIAN KEPEGAWAIAN RUMAH SAKIT UMUM DAERAH UNDATA PROVINSI SULAWESI TENGAH - Laledak, Sulastri (Katalogis, 2018)
This study aims to describe and analyze the discipline of civil servants employment of civil servants in the general hospital area of Central Sulawesi province. The theory used as a foothold of analysis is the theory of veitzhal rivai which consists of five aspects namely the level of attendance, obedience to work rules, adherence to work standards, high levels of vigilance and ethical work.The research method used is qualitative research with descriptive method where the informant is five people and chosen pursuant to purpossive that is chosen with certain consideration and purpose. Data collection techniques consist of interviews, observation and documentation. The results showed that the discipline of employees from the five aspects studied there are three aspects of the implementation has not run properly, the first presence, which is seen from absenteeism is still low, the second from the aspect of obedience to work regulations is still less this can be seen from the number of employees who do not pay attention Work regulation, the third of the aspects of high awareness level is also still not good, judging from the use of office facilities that are not in place. While in the fourth aspect of adherence to the standard work is very good, this can be seen where the employees in the work refers to technical instructions so that in completing the work the results have been maximized. Fifth, from the aspect of ethical work is also very good, it is seen from employees who show good behavior and attitude in accordance with ethics in general.